Effect of Giving Lamtoro Leaf Extract and Pruning on Cucumber Plant Production (Cucumis Sativus L.) - Robert A. Sole; Henny A. Raga; Uly J. Riwukaho; Joritha Naisanu; Astrid Aryani Ndun; Nur Aini Bunyani; Darmanto F. Kisse (Jurnal Biologi Tropis, 2022)
Cucumber (Cucumis sativus L.) has a fairly good nutritional content and is in great demand by the public. Cucumber production in NTT continues to increase, but it is still low when compared to national production data. One of the efforts made is to use liquid organic fertilizers that are cheap and easy to get around us because they come from natural ingredients, namely plant residues or animal remains. Lamtoro leaf extract (Leucaena leucocephala, Ssp) is an organic fertilizer made from plants that is environmentally friendly. In addition to the fertilization factor, pruning activities are also needed to increase the weight of cucumber production. Pruning is a common cultivation action to limit excessive vegetative growth in plants so that nutrients or nutrients can be absorbed by the parts of plants that need them optimally. These nutrients can be provided by lamtoro leaf extract, then pruning is also carried out in order to reduce photosynthetic competition in order to increase cucumber production. Based on this description, it is felt that it is necessary to conduct research on the effect of giving concentration of lamptoro leaf extract and pruning on cucumber plant production. The purpose of this study was to determine the interaction of giving lamptoro leaf extract concentration and pruning on cucumber plant yields. This research was conducted from May to June 2022. This study was arranged using a randomized block design (RBD) in a factorial pattern with two factors. The first factor was the application of lamtoro leaf extract fertilizer consisting of four levels, namely: L0: control (without lamtoro leaf extract), L1: 400 cc of lamtoro leaf extract liter of water-1 plot-1, L2: 450 cc of lamtoro leaf extract liter of water-1 plot-1, L3: 500 cc of lamtoro leaf extract liter of water-1 plot-1. The second factor is pruning (P) consisting of three treatment levels, namely: P0: No pruning, P1: Pruning one leaf and one branch on segments 6–12, P2: Pruning two leaves and two branches on segments 6–12. The results obtained: administration of 500 cc of lamtoro leaf extract liter of water-1 plot-1 and pruning of two leaves and two branches on segments 6–12 of cucumber plants had a very significant effect on cucumber plant yields, concentration of 500 cc of lamtor leaf extract lamtoro liter of water-1 plot-1 and pruning two leaves and two branches on 6–12 plant nodes produced the best growth and yield of cucumber plants, the interaction between lamtor leaf extract and pruning resulted in plant length 79.33, fruit weight 284.83 g, fruit length 30 cm and fruit diameter of 4.48 cm. Recommendation: for cucumber cultivation, it is better to use POC of lamtor leaf extract 500 cc of lamtoro leaf extract liter of water-1 plot-1 and pruning of two leaves and two branches on internodes 6-12 plants. There needs to be further research on the use of POC concentrations of lamtoro leaf extract with higher concentrations to reduce the use of inorganic fertilizers.